SIGNIFICANCE OF YOGA AND MEDITATION IN INDIAN TRADITIONAL GAME MALLKHAMB - Nalawade, Suresh; Powar, Tushar Krishnat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Yoga’s incorporation of meditation and breathing can help to improve a persons mental and physical well being. regular yoga practice creates mental clarity and calmness, increases body awareness, relaxes Mind, sharpens concentration, increase flexibility and muscle strength.Yoga is the process of gaining self enforcement, self realization and self improvement. Practice of yoga brings up number of benefits to sports person and sports itself. yoga and meditation have been given prominence at the international level. yoga and meditation play very crucial role in Indian traditional game mallakhamb. Mallakhamb is a traditional sport, originating from the Indian subcontinent, in which a gymnast performs aerial yoga or gymnastic postures and wrestling grips in concert with a vertical stationary or hanging wooden pole, cane, or rope. The word Mallakhamb also refers to the pole used in the sport. Yoga and meditation are closely related to mallakhamb. Yoga Asanas are Performed on mallakhamb. with the practice of meditation Asanas which need concentration, stability can be easily presented on the mallakhamb.The purpose of the study is to analyse the significance or uses of yoga and meditation in traditional game mallakhamb.